The Enigmatic Role of Lipids in Cilia Signaling - Nechipurenko, Inna V. (Frontiers in Cell and Developmental Biology, 2020)
Primary cilia are specialized cellular structures that project from the surface of most cell types in metazoans and mediate transduction of major signaling pathways. The ciliary membrane is contiguous with the plasma membrane, yet it exhibits distinct protein and lipid composition, which is essential for ciliary function. Diffusion barriers at the base of a cilium are responsible for establishing unique molecular composition of this organelle. Although considerable progress has been made in identifying mechanisms of ciliary protein trafficking in and out of cilia, it remains largely unknown how the distinct lipid identity of the ciliary membrane is achieved. In this mini review, I summarize recent developments in characterizing lipid composition and organization of the ciliary membrane and discuss the emerging roles of lipids in modulating activity of ciliary signaling components including ion channels and G protein-coupled receptors.